PERAN GURU PPKN DALAM UPAYA MENINGKATKAN KEDISIPLINAN SISWA DI SEKOLAH (STUDI KASUS DI SMA NEGERI 1 CIBAL, KEC CIBAL, KAB MANGGARAI) - Verasiana Murni; I Wayan Kertih; I Made Yudana (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aims to determine the role of Civics Teachers in Efforts to Improve Student Discipline. The location of this research was carried out at SMA N 1 Cibal. This study uses a case study design with the Miles and Huberman qualitative model method. The subjects in this study were school principals, students, PPKn teachers, and students. The data collection method used the instruments of observation, interviews, and documentation, then the data analysis method was through: data collection, data reduction, data presentation, and drawing conclusions. The research results show: (1) where SMA N 1 Cibal has strict rules and sanctions consisting of 10 regulations that have their own points. (2) Efforts made by PPKn teachers in an effort to improve student discipline have been good through: enforcement of strict rules and sanctions, instilling awareness in students, exemplary teachers, through socialization, giving punishment, teachers always reminding students about discipline. (3) Supporting and inhibiting factors for PPKn teachers in an effort to improve student discipline: a) supporting factors for the existence of strict rules and sanctions, good physical condition of students, awareness from within students, teachers always reflect a disciplined attitude, the establishment of good relationships between teachers and students. b) Inhibiting factors for the diverse student environment, stubborn students, lack of parental support, lack of parental supervision, student association.